Putative Cut‐Points in Sarcopenia Components and Incident Adverse Health Outcomes: An SDOC Analysis - Cawthon, Peggy M.; Manini, Todd; Patel, Sheena M.; Newman, Anne; Travison, Thomas; Kiel, Douglas P.; Santanasto, Adam J.; Ensrud, Kristine E.; Xue, Qian‐Li; Shardell, Michelle; Duchowny, Kate; Erlandson, Kristine M.; et al. (Journal of the American Geriatrics Society (JAGS), 2020)
OBJECTIVES Analyses performed by the Sarcopenia Definitions and Outcomes Consortium (SDOC) identified cut‐points in several metrics of grip strength for consideration in a definition of sarcopenia. We describe the associations between the SDOC‐identified metrics of low grip strength (absolute or standardized to body size/composition); low dual‐energy x‐ray absorptiometry (DXA) lean mass as previously defined in the literature (appendicular lean mass [ALM]/ht2); and slowness (walking speed <.8 m/s) with subsequent adverse outcomes (falls, hip fractures, mobility limitation, and mortality). DESIGN Individual‐level, sex‐stratified pooled analysis. We calculated odds ratios (ORs) or hazard ratios (HRs) for incident falls, mobility limitation, hip fractures, and mortality. Follow‐up time ranged from 1 year for falls to 8.8 ± 2.3 years for mortality. SETTING Eight prospective observational cohort studies. PARTICIPANTS A total of 13,421 community‐dwelling men and 4,828 community‐dwelling women. MEASUREMENTS Grip strength by hand dynamometry, gait speed, and lean mass by DXA. RESULTS Low grip strength (absolute or standardized to body size/composition) was associated with incident outcomes, usually independently of slowness, in both men and women. ORs and HRs generally ranged from 1.2 to 3.0 for those below vs above the cut‐point. DXA lean mass was not consistently associated with these outcomes. When considered together, those who had both muscle weakness by absolute grip strength (<35.5 kg in men and <20 kg in women) and slowness were consistently more likely to have a fall, hip fracture, mobility limitation, or die than those without either slowness or muscle weakness. CONCLUSION Older men and women with both muscle weakness and slowness have a higher likelihood of adverse health outcomes. These results support the inclusion of grip strength and walking speed as components in a summary definition of sarcopenia. J Am Geriatr Soc 68:1429‐1437, 2020. See related editorial by Cesari et al in this issue